Feeding preferences of the willow sawfl y Nematus oligospilus (Hymenoptera: Tenthredinidae) for commercial Salix clones Preferencias alimentarias de la avispa sierra de los sauces Nematus oligospilus (Hymenoptera: Tenthredinidae) por clones de Salix comerciales - Verónica Loetti; Alejandra Rubio; María Isabel Bellocq (Revista de la Sociedad Entomológica Argentina, 2012)
Nematus oligospilus Förster (Hymenoptera: Tenthredinidae) is a willow sawfly native to the Northern Hemisphere which became a serious defoliator in willow plantations (Salix spp.) of the Southern Hemisphere after being introduced in the early 1980´s. Studies on host preferences provide useful information for the development of pest management strategies where the willow sawfly may produce tree damage and economic loss. Feeding preferences of N. oligospilus larvae were evaluated in laboratory trials by simultaneously offering leaves from four willow tree clones commonly used in commercial plantations in Argentina (Salix babylonica var sacramenta Hortus, Salix nigra Marsch., S. babylonica L. x Salix alba L. 131-27 and Salix matsudana Koidz. x S. alba L. 13-44). Larvae of N. oligospilus fed on leaves from the four clones. However, insects consumed a significantly higher proportion of S. babylonica var sacramenta leaves than of leaves from the other clones. Results indicate that all clones used in the trials were palatable to the insect, and that S. babylonica var sacramenta is the preferred host for larval herbivory. Nematus oligospilus Förster (Hymenoptera: Tenthredinidae), o la avispa sierra de los sauces, es nativa del Hemisferio Norte y se ha convertido en un serio defoliador en plantaciones de sauces (Salix spp.) del Hemisferio Sur, después de su introducción a principios de 1980. Los estudios sobre las preferencias de hospedador aportan información útil para el desarrollo de estrategias, donde la avispa sierra puede producir daño a los árboles y pérdidas económicas. Se evaluó la preferencia alimentaria de las larvas de N. oligospilus, mediante ensayos de laboratorio; se ofrecieron en forma simultánea hojas de cuatro clones de sauce, usados comúnmente en plantaciones comerciales en Argentina (Salix babylonica var sacramenta Hortus, Salix nigra Marsch., S. babylonica L. x Salix alba L. 131-27 and Salix matsudana Koidz. x S. alba L. 13-44). Las larvas de N. oligospilus se alimentaron de las hojas de los cuatro clones. Sin embargo, consumieron una proporción significativamente mayor de las hojas de S. babylonica var sacramenta. Estos resultados indican que todos los clones utilizados en los ensayos fueron palatables para el insecto y que S. babylonica var sacramenta es el hospedador preferido para la herbivoría de las larvas.